2012
DOI: 10.1073/pnas.1114368109
|View full text |Cite|
|
Sign up to set email alerts
|

Differential regulation of the activity of deleted in liver cancer 1 (DLC1) by tensins controls cell migration and transformation

Abstract: The epithelial growth factor receptor plays an important role in cell migration and cancer metastasis, but the underlying molecular mechanism is not fully understood. We show here that differential regulation of the rhodopsin-GTPase-activating (Rho-GAP) activity of deleted in liver cancer 1 (DLC1) by tensin3 and COOH-terminal tensin-like protein (cten) controls EGF-driven cell migration and transformation. Tensin3 binds DLC1 through its actin-binding domain, a region that is missing in cten, and thereby releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
102
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(113 citation statements)
references
References 32 publications
7
102
4
Order By: Relevance
“…Supporting the proposed role of DLC1 as an inhibitor of cell migration and metastasis previously described in a number of cancers, 22,23,27,31,37,38 we here found that DLC1 expression was reduced in metastatic melanoma compared with primary melanoma and nevi. Moreover, nuclear DLC1 expression was further down in primary melanomas compared with normal nevi, suggesting that loss of nuclear DLC1 may be an earlier event than cytoplasmic DLC1 loss in melanoma.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Supporting the proposed role of DLC1 as an inhibitor of cell migration and metastasis previously described in a number of cancers, 22,23,27,31,37,38 we here found that DLC1 expression was reduced in metastatic melanoma compared with primary melanoma and nevi. Moreover, nuclear DLC1 expression was further down in primary melanomas compared with normal nevi, suggesting that loss of nuclear DLC1 may be an earlier event than cytoplasmic DLC1 loss in melanoma.…”
Section: Discussionsupporting
confidence: 69%
“…29 It is well established that DLC1 is recruited to the focal adhesions via interactions between its FAT domain and the SH2 domains of the tensin proteins, which have moreover been found to differentially regulate DLC1 activity in vitro. 30,31 Our group has recently found that one tensin family member, Cten, is upregulated in the progression from melanocytic nevi to primary tumors, 32 and display oncogenic properties in vitro (unpublished data). This, along with the numerous studies showing DLC1 downregulation in cancer, prompted us to examine the expression profile of DLC1 in melanoma, as a first step to characterize its role in melanoma progression and metastasis.…”
mentioning
confidence: 99%
“…It has been shown that, upon EGF stimulation, there is an expression switch from tensin3 to cten, leading to a drastic increase in active RHOA along the edges of a cell undergoing random migration. This effect of the tensin3/cten switch has been believed to be mediated via their ability to interact with DLC1 and the inability to activate it (16). The activation of ERK, however, was seen to have no apparent effect on DLC1 at the transcript levels.…”
Section: Discussionmentioning
confidence: 80%
“…In addition to its RHOGAP domain, DLC1 contains the sterile alpha motif (SAM) and steroidogenic acute regulatory protein (StAR)-related lipid transfer protein modules and a unique serinerich region (SRR). The START (12,13), RHOGAP (14), SAM (15,16) and SRR regions have been implicated in the regulation of cell morphology, migration, and tumor suppression.…”
mentioning
confidence: 99%
“…Furthermore, the GAP activities of both srGAP2 and plexins are autoinhibited and activated by induced dimerization, implicating a GAP activation mechanism that is regulated by intermolecular interactions. Indeed, the RhoGAP activity of DLC1 has been shown to be inhibited by an intramolecular interaction with its SAM domain 34 , and association between the DLC1 SAM domain and tensin3 releases an autoinhibitory interaction in DLC1, thereby increasing its RhoGAP activity. Our data show that phosphorylation of DLC1 at Ser549 contributes to the association between DLC1 and tensin2 ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%